2013
DOI: 10.1080/07315724.2013.791167
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Method for Measuring Blood Ascorbate Concentrations in Patients Receiving High-Dose Intravenous Ascorbate

Abstract: Objective A simple method of using fingerstick blood glucose monitors (FSBG) to estimate blood ascorbate values after high-dose intravenous (IV) ascorbate infusion is evaluated as a substitution for HPLC measurement. Methods In 33 participants, readings from FSBG were taken before and after IV ascorbate infusions at various time points, with the post-infusion FSBG readings subtracted by the baseline glucose readings. The results of the subtractions (AAFSBG) were correlated with ascorbate concentrations detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
(24 reference statements)
0
10
0
3
Order By: Relevance
“…It is noted that care must be taken in patients with diabetes because AA can falsely elevate glucometer readings substantially (ie, values can range greater than 400 mg/dL). 35 Pharmacokinetic studies have generally observed an elimination half-life of approximately 2 hours, 15 , 36 with the implication that glucometer readings could remain abnormal for 6 to 8 hours postinfusion. Thus, it is important to remind patients with diabetes to be cautious with regard to treating themselves with added insulin if readings remain elevated after receiving IV AA.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that care must be taken in patients with diabetes because AA can falsely elevate glucometer readings substantially (ie, values can range greater than 400 mg/dL). 35 Pharmacokinetic studies have generally observed an elimination half-life of approximately 2 hours, 15 , 36 with the implication that glucometer readings could remain abnormal for 6 to 8 hours postinfusion. Thus, it is important to remind patients with diabetes to be cautious with regard to treating themselves with added insulin if readings remain elevated after receiving IV AA.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that high plasma vitamin C concentrations interfere with most skin-prick or blood glucose measurements by generating either a falsely high or falsely low result [ 49 , 50 ]. For this reason, it is important not to measure (or if inadvertently measured, discount) the blood glucose concentration indicated by such tests until 12 hours after an IVC infusion has ended.…”
Section: Discussionmentioning
confidence: 99%
“…Cara alternatif untuk mengukur kadar vitamin C serum masih sedang dipelajari, salah satunya adalah mengukur kadar vitamin C dalam glukosa darah. 29 Pemeriksaan koagulasi juga dapat dilakukan untuk menyingkirkan kemungkinan gangguan perdarahan. Pemeriksaan sederhana PT/APTT (yang biasanya lebih mudah dilakukan dibanding von Willebrand Factor/ vWF) dapat dilakukan untuk menyingkirkan diagnosis selain penyakit skorbut.…”
Section: Pemeriksaan Penunjang Skorbut Pada Thalassemiaunclassified